Application of an in vitro neuroinflammation model to evaluate the efficacy of magnesium-lithium alloys - Bhat, Krathika; Helmholz, Heike; Willumeit-Römer, Regine (Frontiers in Cellular Neuroscience, 2024)
Mg-Li alloys can be promising candidates as bioresorbable Li-releasing implants for bipolar disorder and other neurodegenerative disorders. In order to compare the therapeutic efficacy of conventional Li salts and Li delivered through Mg-Li alloy extracts, we tested an in vitro model based on the neuroinflammation hypothesis of mood disorders (peripheral inflammation inducing neuroinflammation) wherein, a coculture of microglia and astrocytes was treated with conditioned medium from pro-inflammatory macrophages. Two alloys, Mg-1.6Li and Mg-9.5Li, were tested in the form of material extracts and well-known outcomes of Li treatment such as GSK3β phosphorylation (indirect flow cytometry) and influence on inflammation-related gene expression (qPCR) were compared against Li salts. This is the first study demonstrating that Li can increase the phosphorylation of GSK3β in glial cells in the presence of excess Mg. Furthermore, Mg-Li alloys were more effective than Li salts in downregulating IL6 and upregulating the neurotrophin GDNF. Mg had no antagonistic effects towards Li-driven downregulation of astrogliosis markers. Overall, the results provide evidence to support further studies employing Mg-Li alloys for neurological applications.